Strategi Bisnis Unit dalam Pendekatan SWOT untuk Meningkatkan Daya Saing di Pasar Global - Yumita, Yumita; Khaerunnisa, Syarifa; Awaluddin, Murtiadi; Sudirman, Sudirman (Lembaga Yasin AlSys, 2025)
This research aims to analyze the business unit's strategy in facing dynamic market competition. The focus of the research is to identify internal and external factors that affect the performance of the business unit and evaluate the effectiveness of the strategies implemented. The research used a qualitative approach with a case study method on one of the business units in a particular sector, such as manufacturing or technology. Data was collected through in-depth interviews with business unit managers, analysis of financial statements, and literature review. The results showed that the strategies of product differentiation, operational optimization, and adaptation to technology were key elements to improve the competitiveness of the business unit. SWOT analysis revealed key strengths, such as product innovation capabilities, but also indicated threats from the emergence of new competitors. The study emphasizes the importance of synergy between strategic vision, innovation, and efficiency in supporting business sustainability. The study provides strategic recommendations for other business units looking to improve their competitiveness in the global market. The findings suggest that the right strategy can help businesses be more adaptive to market dynamics and maintain relevance in an increasingly competitive era.